The relationship between indices and Kuala Lumpur syariah index / Ungku Zareen Ungku Zolkipli - Ungku Zolkipli, Ungku Zareen (Faculty of Business Management, 2014)
This research will investigate the relationship between Kuala Lumpur Shariah Index and the macroeconomic variables. Generally, the research purpose is to observe the relationship in Malaysian context. In order to achieve the objective, multiple linear regression (MLR) are used to created research model. The variables involved in this research are, Kuala Lumpur Shariah Index (KLSI), Consumer Price Index (CPI), FTSE Bursa Malaysia Hijrah Index (FBMHI), Kuala Lumpur Composite Index (KLCI), and Dow Jones Islamic Index (DJII). The data used is a monthly data which is from February 2007 until July 2014. The research finding showed that KLSI are determined only by the shariah stock market variables such as FBMHI and DJII.